Neutrino masses and mixing in brane-world theories - Lukas, A; Ramond, P; Romanino, A; Ross, G (2001)
We present a comprehensive study of five-dimensional brane-world models for neutrino physics based on flat compactifications. Particular emphasis is put on the inclusion of bulk mass terms. We derive a number of general results for such brane-world models with bulk mass terms. In particular, in the limit of small brane-bulk couplings, the electroweak eigenstates are predominantly given as a superposition of three light states with non-trivial small admixtures of bulk states. As a consequence, neutrinos can undergo standard oscillations as well as oscillation into bulk Kaluza-Klein states. We use this structure to construct a specific model based on ℤ2 orbifolding and bulk Majorana masses which is compatible with all observed oscillation phenomena. The solar neutrino deficit is explained by oscillations into sterile bulk states while the atmospheric neutrino deficit is due to νμ - ντ oscillations with naturally maximal mixing. In addition, the model can accommodate the LSND result and a significant neutrino dark matter component. We also analyze the constraints from supernova energy loss on neutrino brane-world theories and show that our specific model is consistent with these constraints.